A Study Of Viruddha-Ahar In Healthy Lifestyle W.S.R. Incompatible Foods - Choudhary, Prakash; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra; Saini, Mukesh (International Research Journal of Ayurveda & Yoga, 2021)
In Ayurvedic works of art, Ahara (food) is referenced as one among the three Upasthambas (Sub mainstays of the body) which upholds the three principles Sthambas (Pillars) of the body. Ahara is viewed as indispensable for the human body as it gives the fundamental supplements, which are extremely crucial for complete the essential exercises of absorption and digestion. Viruddha Ahara is an interesting idea portrayed in Ayurveda. Ayurveda plainly characterizes that specific eating routine and its blends, which intrude on the digestion of tissue, which hinders the course of development of tissue and which have the contrary property to the tissue are called as Viruddha Anna or incongruent eating regimen. Diet ought to be healthy just as per Desh, Kala, Prakriti, and Vayah. Diet assumes a significant part in our life. Ayurveda has depicted Aahara exhaustively in their different Granthas. The food which isn’t right in blend, which has gone through wrong handling, which is burned-through in mistaken portion, which is burned-through in the erroneous season of day and the wrong season, can prompt Viruddha Ahara. Food taken in legitimate technique feeds the individual genuinely and intellectually both and it is the food through which individual achieves positive wellbeing and development of the body. Food taken in ill-advised (Unbalanced) strategies can cause different sorts of sicknesses. Thusly Ayurveda has given sharp consideration to idea of healthy ahara and unwholesome ahara. Correspondingly admission of contrariness food is a lot of expansions in present time.